2020
DOI: 10.1017/s0950268820001235
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: asymptomatic carrier transmission is an underestimated problem

Abstract: At the present time, COVID-19 is spreading rapidly [1]. The global prevention and control of COVID-19 is focused on the estimation of the relevant incubation period, basic reproduction number (R0), effective reproduction number (Rt) and death risk. Although the prevention and control of COVID-19 requires a reliable estimation of the relevant incubation period, R0, Rt and death risk. Another key epidemiological parameter-asymptomatic ratio that provides strength and range for social alienation strategies of COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
137
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(141 citation statements)
references
References 11 publications
0
137
0
4
Order By: Relevance
“…Many values were estimated to fit the beginning of expansion of disease in France, other were inferred from expert opinions, see Section 'Model parameters'. The proportion (1 − f ) ranges from 17.9% to 86% [1,[17][18][19][20] and some reviews therein [21]. The lower value was observed on board of the Diamond princess, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many values were estimated to fit the beginning of expansion of disease in France, other were inferred from expert opinions, see Section 'Model parameters'. The proportion (1 − f ) ranges from 17.9% to 86% [1,[17][18][19][20] and some reviews therein [21]. The lower value was observed on board of the Diamond princess, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Value of parameter f: Recall that, (1 − f ) stands for the fraction of exposed individuals that becomes unreported infectious and corresponds to the proportion of asymptomatic or silent carriers or mild infectious. (1 − f ) ranges from 17.9% to 86% [1,[17][18][19][20] and some reviews therein [21]. The fractions of unreported individuals in these previous studies are derived from the number of tests performed.…”
Section: Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 asymptomatic infections refer to those positive in nucleic acid testing with nasopharyngeal swabs but developing no novel coronavirus-related symptoms, such as fever, upper respiratory symptoms (cough and sore throat), fatigue, and gastrointestinal symptoms (for example, diarrhea). They are not referred to as "patients" due to the lack of symptoms [6], but they spread the virus easily while keeping frequent contact with others due to their unawareness of the infection [6,23]. The main reasons for asymptomatic infections might be that the infections are yet to develop clinical manifestations in the early stage of disease treatment or the individuals are strongly immune and develop no clinical manifestations after infection [24].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 showed typical respiratory symptom (such as fever, cough and lung damage) and some other symptoms such as fatigue, myalgia, and diarrhea 2 . Many studies have found that even asymptomatic people also have strong infectivity 3,4 . At present, speci c antiviral drugs or vaccines currently have not been available for the treatment.…”
mentioning
confidence: 99%